A mitochondria-targeting lipid-small molecule hybrid nanoparticle for imaging and therapy in an orthotopic glioma model - Menghuan Tang; Kai Lin; Mythili Ramachandran; Longmeng Li; Hongye Zou; Huzhi Zheng; Zhao Ma; Yuanpei Li (Elsevier, 2022)
Hybrid lipid‒nanoparticle complexes have shown attractive characteristics as drug carriers due to their integrated advantages from liposomes and nanoparticles. Here we developed a kind of lipid-small molecule hybrid nanoparticles (LPHNPs) for imaging and treatment in an orthotopic glioma model. LPHNPs were prepared by engineering the co-assembly of lipids and an amphiphilic pheophorbide a‒quinolinium conjugate (PQC), a mitochondria-targeting small molecule. Compared with the pure nanofiber self-assembled by PQC, LPHNPs not only preserve the comparable antiproliferative potency, but also possess a spherical nanostructure that allows the PQC molecules to be administrated through intravenous injection. Also, this co-assembly remarkably improved the drug-loading capacity and formulation stability against the physical encapsulation using conventional liposomes. By integrating the advantages from liposome and PQC molecule, LPHNPs have minimal system toxicity, enhanced potency of photodynamic therapy (PDT) and visualization capacities of drug biodistribution and tumor imaging. The hybrid nanoparticle demonstrates excellent curative effects to significantly prolong the survival of mice with the orthotopic glioma. The unique co-assembly of lipid and small molecule provides new potential for constructing new liposome-derived nanoformulations and improving cancer treatment.